1996
DOI: 10.1161/01.res.78.5.750
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH and Tyrosine Phosphorylation but Not Calcium Determine Shear Stress–Induced Nitric Oxide Production in Native Endothelial Cells

Abstract: Signalling pathways determining the shear stress-induced production of NO from endothelial cells in situ were investigated using a bioassay system in which shear stress was increased by inducing vasoconstriction in an endothelium-intact donor segment (rabbit iliac artery) while maintaining a constant luminal perfusion rate. Shear stress-induced NO production, as assessed by changes in the tone of a preconstricted endothelium-denuded detector ring, was biphasic and consisted of an initial transient (20- to 25-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
274
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(291 citation statements)
references
References 29 publications
14
274
1
2
Order By: Relevance
“…Indeed, most humoral ligands including bradykinin, acetylcholine, and ATP stimulate NO production from eNOS by raising the level of intracellular Ca 2ϩ , which forms Ca 2ϩ /CaM complex (34). On the other hand, mechanical forces such as fluid shear stress and stretching stimulate NO production from eNOS by Ca 2ϩ -independent mechanisms (1,10). Moreover, eNOS has been shown to be regulated by interactions with other positive and negative protein modulators such as caveolin and heat shock protein 90 (20,41).…”
mentioning
confidence: 99%
“…Indeed, most humoral ligands including bradykinin, acetylcholine, and ATP stimulate NO production from eNOS by raising the level of intracellular Ca 2ϩ , which forms Ca 2ϩ /CaM complex (34). On the other hand, mechanical forces such as fluid shear stress and stretching stimulate NO production from eNOS by Ca 2ϩ -independent mechanisms (1,10). Moreover, eNOS has been shown to be regulated by interactions with other positive and negative protein modulators such as caveolin and heat shock protein 90 (20,41).…”
mentioning
confidence: 99%
“…The mechanism of the shear stress-evoked relaxation in intact rat aorta is therefore at present unclear. It may involve changes in cytosolic pH as demonstrated in response to changes in shear stress in cultured cells from this vessel (Ziegelstein et al 1992(Ziegelstein et al , 1998 or activation of tyrosine kinases as suggested in cultured endothelium from other species (Ayajiki et al 1996). Al-Mehdi, A.…”
Section: Discussionmentioning
confidence: 88%
“…However, a number of investigators were unable to detect any changes in endothelial [Ca¥]é and have proposed other mechanisms of mechanotransduction. These include shear stress-evoked protein tyrosine phosphorylation (Ayajiki et al 1996) and changes in endothelial cytosolic pH. In cultured rat aortic endothelium, increased shear stress has been reported to evoke cytosolic acidification (Ziegelstein et al 1992), whilst an abrupt reduction in shear stress results in alkalinisation due to activation of Na¤-dependent Cl¦-HCOצ exchange and Na¤-H¤ exchange (Ziegelstein et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both transient and sustained release of NO has been reported in response to this shear stress. It is seems that shear stress regulates NO release in a Ca 2+ -independent mode through phosporylation of eNOS, which results in a sustained basal NO production irrespective of the presence or absence of the Ca 2+ transient effect [87][88][89]. Kutchan and Frangos [90] measured the NO end-oxidation products ( -2 NO and -3 NO ) released from endothelial cells exposed to laminar flow and reported the presence of transient Ca 2+ -dependent NO release at the initial moment but sustained release in the presence of a constant shear stress level.…”
Section: Blood Flow Distribution Among Different Vascular Beds Is Regmentioning
confidence: 99%